KERUKUNAN UMAT BERAGAMA DI KAMPUNG SAWAH KECAMATAN PONDOK MELATI KOTA BEKASI - Muhammad Agus Noorbani (Al-Qalam, 2019)
This article tries to explain statement of Ashutosh Varshney that says communal violence is a rural phenomenon and if violence does occur it will be concentrated locally. There are areas that have high rate of violence but there are other areas with low rate of violence and even devoid of communal violence and conflicts. Using qualitative case study design, this research tries to know the social  mechanism that creates peace in the inter religion relation in Kampung Sawah to be well-maintained. This research especially aims to know the challenges faced by the people of  Kampung Sawah in keeping peaceful condition in inter-religion relation. This research finds that peace among inter-religion relation in Kampung sawah has been maintained  up to the present is the result of activities which have been conducted since a long time ago, even since Kampung Sawah area was first built. The role of kinship ties, society and religious figures and the social capital existing in Kampung Sawah secara berkelindan makes Kampung Sawah able to maintain peaceful condition up to the present. The challenges facing the people of Kampung Sawah in maintaining peace among religious communities at the moment at least encompasses two things; the  fast flow of information through social media and the high rate of population growth of migrants who are boxed in exclusive housing blocks.